Microbial populations on brewery filling hall surfaces – Progress towards functional coatings. (September 2015) - Priha, Outi; Raulio, Mari; Cooke, Kevin; Fisher, Leanne; Hill, Claire; Hylkinen, Silja; Kelly, Peter; Navabpour, Parnia; Ostovarpour, Soheyla; Tapani, Kaisa; Tattershall, Carin; Vehviläinen, Anna-Kaisa; et al.
Abstract: Microbial populations on equipment surfaces of beverage filling lines were investigated as a function of surface coating type, location and time. Photocatalytic metal-ion doped (Ag or Mo) and non-doped TiO2 coatings deposited using reactive magnetron sputtering and spray coating methods were studied as means to reduce microbial numbers accumulating on the surfaces. The coatings were applied to stainless steel coupons, which were mounted to one canning and one glass bottle filling line for 3–5 months. After exposure microbial numbers on the coupons were evaluated by culturing, and bacterial community profiles were characterised with PCR-DGGE (denaturing gradient gel electrophoresis). The results showed that the longer the run time after washes the higher microbial numbers were detected, and that the two filling lines each had their characteristic bacterial community. The major species identified were members of Acinetobacter sp., lactic acid bacteria and enterobacteria. No clear effect of the different coating materials on the microbial numbers or bacterial community composition on the surfaces was shown. In conclusion, functional coatings with sufficient mechanical and chemical durability for industrial surfaces have been developed. Although these coatings have been previously reported to reduce the number of microorganisms on the surfaces in vitro, their efficacy in the challenging beverage process conditions was not proven. Highlights: Microbial numbers on process surfaces followed the time from last washing cycle. Each filling line had a characteristic bacterial community. The major microbial groups were Acinetobacter sp., LAB and enterobacteria. Coatings were not shown to function in the challenging beverage process conditions.